2011
DOI: 10.1051/0004-6361/201015259
|View full text |Cite
|
Sign up to set email alerts
|

Detectability of ultrahigh energy cosmic-ray signatures in gamma-rays

Abstract: The injection of ultrahigh energy cosmic-rays in the intergalactic medium leads to the production of a GeV-TeV gamma-ray halo centered on the source location, through the production of a high electromagnetic component in the interactions of the primary particles with the radiation backgrounds. This paper examines the prospects for the detectability of such gamma-ray halos. We explore a broad range of astrophysical parameters, including the inhomogeneous distribution of magnetic fields in the large-scale struct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 69 publications
1
21
0
Order By: Relevance
“…This possibility has been previously studied for proton sources in Refs. [51][52][53][54] and has been revived recently in the context of unusually bright though distant TeV γ-ray sources [55][56][57]. Here we extend the discussion to the case of UHE CR nuclei and study the effect of IGMFs on the observability of the PS flux in detail.…”
Section: Point-source Fluxmentioning
confidence: 82%
“…This possibility has been previously studied for proton sources in Refs. [51][52][53][54] and has been revived recently in the context of unusually bright though distant TeV γ-ray sources [55][56][57]. Here we extend the discussion to the case of UHE CR nuclei and study the effect of IGMFs on the observability of the PS flux in detail.…”
Section: Point-source Fluxmentioning
confidence: 82%
“…This possibility was also recently studied in Kotera et al (2011). In both studies, a source at 1 Gpc of luminosity 10 46 erg s −1 above 10 19 eV is found to possibly yield detectable fluxes for Fermi or CTA (for instance, a flux of 10 −9 GeV cm −2 s −1 spread over ∼0.2 deg).…”
Section: Distant Point Sources Of Cosmogenic Uhe Neutrinosmentioning
confidence: 82%
“…In both studies, a source at 1 Gpc of luminosity 10 46 erg s −1 above 10 19 eV is found to possibly yield detectable fluxes for Fermi or CTA (for instance, a flux of 10 −9 GeV cm −2 s −1 spread over ∼0.2 deg). These synchrotron images are promising for the detection of distant UHECR accelerators and have the advantage that they are a signature of the pion production mechanism (see discussions in Gabici & Aharonian 2005;and Kotera et al 2011), unlike cascades in the case of distant sources (see below for the local universe). However, their signal is weaker in the TeV range than in the GeV, although their detection with CTA should still be possible.…”
Section: Distant Point Sources Of Cosmogenic Uhe Neutrinosmentioning
confidence: 99%
“…The second type of gamma-ray signals could be provided by synchrotron radiation, from the pion decay and pair production induced UHE secondary pairs, in the magnetized environment of a source [191,192,193]. In these cases, the detection is most promising for extremely powerful sources located around 1 Gpc, which are less constrained by their contribution to the UHECR flux and would keep an angular size well below 1 degree [194]. Interestingly, GeV-TeV cascades were recently proposed in [195] (and recently re-examined in [177]) as a possible interpretation of the TeV signal observed by HESS in the direction of the AGN 1ES0229+200 (z=0.14).…”
Section: Secondary Cosmogenic Messengersmentioning
confidence: 99%